2021
DOI: 10.1016/j.apsb.2020.12.005
|View full text |Cite
|
Sign up to set email alerts
|

An optimized derivative of an endogenous CXCR4 antagonist prevents atopic dermatitis and airway inflammation

Abstract: Aberrant CXCR4/CXCL12 signaling is involved in many pathophysiological processes such as cancer and inflammatory diseases. A natural fragment of serum albumin, named EPI-X4, has previously been identified as endogenous peptide antagonist and inverse agonist of CXCR4 and is a promising compound for the development of improved analogues for the therapy of CXCR4-associated diseases. To generate optimized EPI-X4 derivatives we here performed molecular docking analysis to identify key interaction motifs of EPI-X4/C… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
68
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(81 citation statements)
references
References 59 publications
13
68
0
Order By: Relevance
“…Finally, the CXCR4/CXCL12 signaling axis plays a pivotal role in numerous biological processes and an overexpression of CXCR4 has been associated with several diseases including skin inflammatory diseases such as psoriasis and AD ( 69 , 70 ). In this sense, it has been recently demonstrated that an endogenous CXCR4 antagonist reduced skin inflammation in an AD mouse model, demonstrating a role for the CXCR4/CXCL12 axis in AD, as well as showing a potential role for CXCR4-antagonizing agents as therapeutic options in skin inflammatory diseases ( 70 ). In addition, higher serum levels of CXCL12 were found in AD patients compared aged-matched healthy controls ( 71 ).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the CXCR4/CXCL12 signaling axis plays a pivotal role in numerous biological processes and an overexpression of CXCR4 has been associated with several diseases including skin inflammatory diseases such as psoriasis and AD ( 69 , 70 ). In this sense, it has been recently demonstrated that an endogenous CXCR4 antagonist reduced skin inflammation in an AD mouse model, demonstrating a role for the CXCR4/CXCL12 axis in AD, as well as showing a potential role for CXCR4-antagonizing agents as therapeutic options in skin inflammatory diseases ( 70 ). In addition, higher serum levels of CXCL12 were found in AD patients compared aged-matched healthy controls ( 71 ).…”
Section: Discussionmentioning
confidence: 99%
“…AMD3100, a CXCR4 antagonist that has been used to mobilize stem cells (Cashen et al, 2007), could be tested in clinical trials. Optimized derivatives of a peptide called EPI-X4, originally discovered because of its ability to inhibit CXCR4-tropic HIV infection of target cells (Zirafi et al, 2015), exhibit superior activity over AMD3100 for blocking CXCR4-mediated chemotaxis and have been shown to potently block migration of immune cells into the lungs of asthmatic mice (Harms et al, 2020). These derivatives are intriguing candidates for treatment of severe COVID-19.…”
Section: Cxcr4 Antagonism As a Target For T Cell-mediated Immunopathogenesis In The Lungsmentioning
confidence: 99%
“…TG-0054 developed and screened for cell mobilization displayed an immune suppressive function in minipigs [ 42 ], however the authors of the paper proposed that the mobilization of stem cells is the cause of this effect. At last, EPI-X4, a natural fragment of albumin and EPI-X4 derived peptides have been shown to inhibit inflammatory cell infiltration in a mouse model of allergic hypereosinophilia [ 43 ] and reduce skin inflammation in a mouse model of atopic dermatitis [ 44 ]. Moreover, these peptides share key interactions at CXCR4 with IT1t [ 45 ].…”
Section: Cxcr4 As Target For Inflammationmentioning
confidence: 99%